A National Collegiate Athletic Association Division I Athlete's Return to Play After Traumatic Knee Dislocation With Vascular and Nerve Injury. (November 2018) - Kolosky, Michael; Spindler, Kurt P.
Abstract : Traumatic knee dislocations are thought to be relatively uncommon; however, they are a devastating injury that can be life altering. A concomitant vascular injury carries a particularly high morbidity rate, with some studies reporting as many as one in five patients losing a limb. Neurologic injury can pose problems as well, in particular for athlete populations that have structure and function as integral parts of their activities. This case study looks at the journey of an elite-level football player (NCAA Division I Pac-12 conference) who sustained a traumatic knee dislocation with vascular and neurologic injury and, eventually, his return to play. The study analyzes the treatment and management course, his ultimate performance after injury, and potential benefits in aiding the management of future knee dislocation with vascular and neurologic injuries.